2017
DOI: 10.1016/j.jinf.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal listeriosis in the UK 2004–2014

Abstract: ObjectiveTo define the clinical features and outcomes of neonatal listeriosis, and identify the maternal risk factors to seek scope for improvement. MethodsNeonatal listeriosis was identified prospectively from a United Kingdom neonatal infection surveillance network (neonIN) between 2004 and 2014. The participating neonatal units completed a study-specific proforma. ResultsThe incidence of neonatal listeriosis was 3.4 per 100,000 live births. Of the 21 cases identified, 19 were confirmed with a median gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 12 publications
1
34
1
Order By: Relevance
“…However, we also observed a high CFR (46.7%) in newborns, although outcome was known only for 38.5% cases and this was not statistically significant (p = 0.79). High fatality rates of listeriosis in newborns were also reported in Lombardy, Italy (30%), and in England (24%) 21 , 22 . Recently, a French study suggested that CFR might be generally higher in pregnancy-related cases than reported to date.…”
Section: Discussionmentioning
confidence: 78%
“…However, we also observed a high CFR (46.7%) in newborns, although outcome was known only for 38.5% cases and this was not statistically significant (p = 0.79). High fatality rates of listeriosis in newborns were also reported in Lombardy, Italy (30%), and in England (24%) 21 , 22 . Recently, a French study suggested that CFR might be generally higher in pregnancy-related cases than reported to date.…”
Section: Discussionmentioning
confidence: 78%
“…Usually, pregnant women, the newborn, elderly people, and immunocompromised individuals are more susceptible to listeriosis, but it may occasionally occur in healthy individuals. The prevalence of listeriosis among pregnant women, neonates, and the elderly is 12, 3.4, and 10 per 100,000, respectively, compared with 0.7 per 100,000 in the general population (Goulet, Hedberg, Le Monnier, & De Valk, ; Sapuan et al., ; Southwick & Purich, ). Listeriosis has an average fatality rate of 20% to 30% even with the application of antibiotic therapy (Swaminathan & Gerner‐Smidt, ).…”
Section: Human Listeriosismentioning
confidence: 99%
“…About half the infants who are infected with L. monocytogenes have no apparent immunocompromising condition [16]. Neonatal listeriosis is associated with an overall case fatality rate of 50% [17], with severe neurological and developmental sequalae observed in 40% of surviving neonates [18]. Due to the severity of the illness, in New Zealand (NZ) all neonates with suspected infection are treated with amoxicillin which targets L. monocytogenes, as well as other infections [19].…”
Section: Introductionmentioning
confidence: 99%